The WD-40 repeat protein PkwA of Thermomonospora curvata is associated with rapid growth and is localized in the tips of growing hyphae - Petříčková, Kateřina; Hašek, Jiří; Benada, Oldřich; Petříček, Miroslav (FEMS microbiology letters, 2006)
The PkwA protein of the thermophilic actinomycete Thermomonospora curvata has already been reported as the first instance of a WD-40 module-containing protein of prokaryotic origin. This protein is composed of an N-terminal eukaryotic-type protein kinase domain and of seven C-terminal WD-40 repeats. PkwA is a peripheral membrane protein that is linked to the early exponential growth phase of the bacterium. Its intracellular concentrations are extremely low. We have shown that the protein forms high molecular weight complexes and is localized mainly in the tips of the young Thermomonospora vegetative hyphae.
Keywords: protein-serin-threoninkinasy; Membrane Proteins; Bacterial Proteins; aminokyselinové motivy; Financing, Organized; Streptomyces coelicolor; Actinomycetales; Hyphae; Protein Serine-Threonine Kinases; bakteriální proteiny; hyfy; membránové proteiny; financování organizované; Amino Acid Motifs